Globalisation and income distribution - Dynamics and structure of income in emerging economies - Jacek Tomkiewicz (Transformation, Integration and Globalization Economic Research (TIGER), 2020)
Goal of the text is to find links between current phase of economic globalisation and income distribution in developing economies. Dynamics and structure of income in so called emerging economies is in the bigger and bigger extend affected by growing international flows of trade and capital. Changing character of global economy makes us to reconsider traditional theories which link international economic relations and income distribution. In both developed and developing economies there are structural forces which favour rising income inequalities. Text has mainly theoretical and descriptive character but statements are supported by the statistical data. The most important findings are as follow. There are no evidences that so called catching-up effect is the common feature in global economy: low level of development does not guarantee high pace economic growth. In the current phase of globalisation there are strong structural causes that lead to rising income inequalities in developing countries, so only state's intervention can secure social cohesion within national economy.
Keywords: D31; F21; F41; 330; Economic development; inequality; developing countries